Clinical and Neuropsychological Differences between Mild Parkinson's Disease Dementia and Dementia with Lewy Bodies - Petrova, Mariya (Dement Geriatr Cogn Dis Extra, 2015)
BACKGROUND: The specific profile of dementia in Parkinson's disease (PDD) and dementia with Lewy bodies (DLB) in the earliest stages of dementia is still unclear and subject of considerable controversy. METHODS: We investigated 27 PDD patients and 24 DLB patients with parkinsonism in the early stage of dementia, i.e. with a Mini-Mental State Examination score of ≥24. RESULTS: Compared to PDD, patients with DLB demonstrated significantly lower scores when testing attention and executive functions [modified card sorting test (p < 0.001) and digit span backward (p < 0.02)], as well as when testing constructive abilities [copy of complex designs (p = 0.001) and pentagon (p < 0.001)]. Using logistic regression analysis, diagnosis was predicted from the cognitive profile, with an overall accuracy of 88.2%. In addition, PDD patients showed a significantly higher Unified Parkinson's Disease Rating Scale (UPDRS) motor subscore (p < 0.001) as well as higher UPDRS motor item scores [tremor at rest (p = 0.01) and bradykinesia (p = 0.001)]. CONCLUSIONS: The cognitive profile in PDD differs from that in DLB in the early stage of dementia, with worse performance on tests of attention and executive functions and constructive abilities in DLB compared to PDD patients. In contrast, motor symptoms are more severe in PDD than in DLB.